On generalized Besov and Campanato spaces - Alieva, L.R.; Gahramanova, Z. Sh.; Rzaev, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the generalized Besov spaces and the spaces defined by the conditions imposed on local oscillations of locally summable functions (in the work, these spaces are called generalized Campanato spaces).